Influence of Emotional Pedagogy on the learning of Mexican High School students. Qualitative study. - Terrazas-Medina, Tamara Isabel (2024)
Objective: to know the influence of Emotional Pedagogy in the development of learning, from the perspective of Mexican high school students. A qualitative, descriptive and cross-sectional study was carried out from March to June 2024, in 5 high schools in Coahuila, Mexico. The sample of 91 participants was obtained from typical cases and the data collection was based on qualitative questionnaires in Forms. The results indicated that some teachers proposed positive learning environments where respect and affectivity were the basis for learning. It seems that a link was found between: the curriculum, which involved the formality of the system; learning, which developed knowledge; and learning, which involved the emotional. It was concluded that Emotional Pedagogy was not rhetoric, but actions full of specific achievements, which resisted the most evident prophecies for the less favored.